The Afghanistan papers: a secret history of the war - Whitlock, Craig (Simon & Schuster)
A Muddled Mission -- "Who Are the Bad Guys?"-- The Nation Building Project -- Afghanistan Becomes an Afterthought -- Raising an Army from the Ashes -- Islam for Dummies -- Playing Both Sides -- Lies and Spin -- An Incoherent Strategy -- The Warlords -- A War on Opium -- Doubling Down -- "A Dark Pit of Endless Money" -- From Friend to Foe -- Consumed by Corruption -- At War with the Truth -- The Enemy Within -- The Grand Illusion -- Trump's Turn -- The Narco-State -- Talking with the Taliban.